INSURANCE INDUSTRY IN SELECTED COUNTRIES IN TRANSITION - Stojakovic, Aleksandra (The European Journal of Applied Economics, 2017)
The main focus of this article is on the insurance sector and economic development of the transition countries, while some of them have already become members of the European Union, others are still in procedure to access  EU. From the data collected with empirical method, it can be seen that the development of the insurance market has positive influence on economic growth. The importance of the insurance sector can be seen in the results of displayed types of insurance from the period 2010 to 2014 year. A confirmation of market development is also located in settled and paid claims that policyholders provide security and confidence in insurance companies.